Optimization of Duplex Real-time PCR to Detect Corynebacterium ulcerans and C. pseudotuberculosis from Patients with Suspected Diphtheria in Jakarta - Usman, Doni; Rosana, Yeva; Yasmon, Andi (Biomedical Journal of Indonesia, 2026)
Introduction. Diphtheria infection remains a serious public health problem in many countries with low vaccine coverage. Molecular detection plays an important role in controlling disease dissemination. Among more than 122 Corynebacterium species, only three are potentially toxigenic: C. diphtheriae, C. ulcerans, and C. pseudotuberculosis. Infections caused by C. ulcerans and C. pseudotuberculosis in humans usually involve close animal contact. Due to the many difficulties in identifying C. ulcerans and C. pseudotuberculosis, this study aimed to optimize Duplex Real-time PCR for rapid and precise detection. Method. Duplex real-time PCR was performed by using 2 pairs of primers and a probe to detect C. ulcerans and C. pseudotuberculosis. All parameters were optimized to maximize PCR amplification. Then, the primer set's specificity was tested against some microorganisms. The sensitivity test of DNA was conducted to get the detection limit. Results: Optimization of real-time PCR was conducted to achieve optimal amplification conditions.  Annealing temperature 57 °C, Optimization of primer and probe concentration of 0.45 μM and 0.50 μM for C. ulcerans, Primer and probe concentrations of 0.35 μM for C. pseudotuberculosis yielded optimal results. The detection limit of DNA of duplex real-time PCR for C. ulcerans was 4.49 DNA copy number and 1.06 DNA copy number for C. pseudotuberculosis. Conclusion. Duplex Real-time PCR optimization result can be used as a detection of C. ulcerans and C. pseudotuberculosis for effective control of dissemination in the population. PCR results showed that all 108 clinical specimens suspect diphtheria were negative for C. ulcerans and C. pseudotuberculosis.